Reduced top‐down attentional control in adolescents with generalized anxiety disorder. Issue 2 (25th December 2020) - Bashford‐Largo, Johannah; Aloi, Joseph; Lukoff, Jennie; Johnson, Kimberly; White, Stuart F.; Dobbertin, Matthew; Blair, Robert James; Blair, Karina S.
Abstract: Background: Generalized anxiety disorder (GAD) can significantly impair quality of life and is associated with a relatively poor long‐term prognosis. Anxiety disorders are often associated with hyper‐responsiveness to threat, perhaps coupled with impaired executive functioning. However, GAD, particularly adolescent GAD, has been the focus of little functional neuroimaging work compared to other anxiety disorders. Here, we examine the neural association of adolescent GAD with responsiveness to threat and response control. Methods: The study involved 35 adolescents with GAD and 34 healthy comparison individuals ( N  = 69) matched on age, gender, and IQ. Participants were scanned during an affective number Stroop task. Results: We found significant Group‐by‐Task Condition interactions in regions involved in response control/motor responding (bilateral precentral gyri and cerebellum) and/or cognitive control/attention (dorsomedial and lateral frontal cortex, posterior cingulate cortex, cuneus, and precuneus). In line with predictions, the youth with GAD showed significantly less recruitment during task trials than the healthy comparison individuals. However, no indications of specific heightened responses to threat were seen. Conclusions: GAD involves reduced capacity for engaging regions involved in response control/motor responding and/or cognitive control/attention. This might reflect either a secondary consequence of the patient's worry or an early risk factor for the development of worry. Abstract : Generalized anxiety disorder (GAD) can significantly impair quality of life and is associated with a relatively poor long‐term prognosis. However, GAD, particularly adolescent GAD has been the focus of little functional neuro‐imaging work compared to other anxiety disorders. Here we examine the neural association of adolescent GAD with responsiveness to threat and response control.